Diagnostic vs therapeutic splenectomy: the trend in tertiary center - Nadarajan, Abinaya R.; Roopavathana S., Beulah; Chase, Suchita; Nayak, Sukria (International Surgery Journal, 2018)
Background: The recent trend being towards spleen preservation, it is necessary to critically analyse the indications for splenectomy and assess if the desired preoperative outcomes are achieved by splenectomy. Methods: This was a retrospective study and patients who underwent elective or emergency splenectomy for various indications in the surgical unit from September 2011 to July 2016 were included. The data was collected from patients records and hospital electronic database. Results: From September 2011 to July 2016, totally 68 patients underwent splenectomy. The indications for therapeutic intervention were splenic abscess (2), splenic cyst (4), trauma (8), ITP (20) and anemia (12). The indications for diagnostic splenectomy were pyrexia of unknown origin in 7 patients and splenomegaly with anemia or pancytopenia in 15 patients. The objective of the operation was achieved in 43 patients (63%). The success rate for each indication: diagnosis (12 of 22 patients, 55%), thrombocytopenia (12 of 20 patients, 60%), anemia (5 of 12 patients, 42%) and as a primary treatment (12 of 14 patients, 86%). Postoperative morbidity within 30days of surgery was seen in 9 patients (13%) and 2 patients (3%) died within 30days of surgery. Conclusions: The indication for splenectomy should be individualized after exploring all other treatment options and based on outcome.